Synthesis of new imidazo[1,2-a]pyridine triazole hybrid molecules as potential apoptotic antitumor agents - Albayrak Halaç, Fatma; Eşsiz, Şebnem; Servili, Burak; Altundaş, Ramazan; Onur Sucu, Bilgesu; Kulu, İrem (John Wiley and Sons Inc, 2024)
Novel imidazo[1,2-a]pyridines bearing 1,2,3-triazole moieties at the C3 position were synthesized. After the characterization of the synthesized compounds, their in vitro therapeutic activities were evaluated in various cancer cell lines (MCF7, A549, HePG2 and T98G). Methoxy substituted derivative was identified as the most potent compound based on the results of its anti-proliferative activity on various cancer cell lines, as well as showing no cytotoxicity on the healthy human fibroblast cell line (MRC-5). As an indicator of apoptosis, a significant decrease in the level of PARP protein was observed in the MCF7 cells treated with this derivative. Molecular docking studies were conducted on wide range of targets such as phosphoinositide 3-kinase (PI3K), cyclin-independent kinase 2 (CDK2), mitogen-activated protein kinase (MEK), insulin-like growth-factor-1 (IGF-1), tubulin, DNA topoisomerase, poly (ADP-ribose) polymerase (PARP) and B-cell lymphoma-2 (BCL2). All the compounds tested showed the lowest binding energies with target PARP1. Moreover, CDK2 and tubulin displayed relatively good binding scores. The docking poses and scores were cross-checked with two different software and multiple protein conformations were included to incorporate flexible protein docking features. Finally, drug-likeness properties of the compounds are further tested via Swiss-ADME software. Novel imidazo[1,2-a]pyridine-1,2,3-triazole derivatives have been synthesized and evaluated for antiproliferative activity against MCF7, A549, HePG2, T98G cell lines. Compound 5c was found to be more potent on PARP protein in MCF7 cell line. The synthesized compounds were docked to PI3K, CDK2, MEK1, IGF-1, TUB1, DNA topoisomerase, PARP1, and BCL2. The best docking poses for PARP1 and CDK2 were obtained from 5c, 5d and 5 f. image
Keywords: Midazo[1,2-a]Pyridine; 1,2,3-Triazole; Anti-Proliferative; PARP; In Silico Molecular Modeling